The Combined Effects of Patient Activation and Relational Aspects on the Quality of Life in Atrial Fibrillation Patients - Wang, Jie; Wang, Qin; Bao, Zhipeng; Peng, Yuanyuan; Liu, Shenxinyu; Yu, Tianxi; Wang, Lin; Yang, Gang; Gao, Min; Sun, Guozhen (Frontiers in Psychology, 2021)
Objective: This study aims to explore the influence of patient activation (PA) and relational aspects on the quality of life (QoL) in patients with Atrial Fibrillation (AF) for developing measures to improve PA and QoL. Methods: A cross-sectional study was undertaken in 2021 among 190 AF patients in Nanjing, China. Research instruments included a self-designed social-demographic characteristics scale, the Patient Activation Measure (PAM), the Atrial Fibrillation Effect on Quality of Life (AFEQT). The data analysis was performed using IBM SPSS 25.0. Spearman correlation analysis, multiple linear regression analysis, and Wilcoxon rank-sum tests were used to assess the association accordingly. Results: The average AFEQT score for the 190 AF patients was 69.32±14.52. The distribution of activation Levels 1, 2, 3, and 4, were where 4.7%, 34.2%, 47.4% and 13.7%, respectively. The multiple linear regression analysis revealed that patient activation, work status, and cardiac rehabilitation of AF patients predicted AF-related QoL (β = 0.270, -0.205, and 0.183, respectively; all P ˂ 0.05). The influences of PA level on subdimensions of AF-related QoL were as follows: symptoms, daily activities and treatment concern. Conclusion: The level of QoL of patients with AF was moderate. Higher levels of patient activation in those with AF were associated with milder symptoms, more positive daily activities and fewer treatment concern. Based on our findings, we suggest that healthcare personnel should encourage AF patients to take active participation in cardiac rehabilitation, disease self-management and foster progression of PA level. Future research is warranted to develop tailor-made interventions aimed at the activation level.